PSII-23 Concurrent supplementation of n-3 polyunsaturated fatty acids impairs C2C12 from the acquisition of functional brown adipocyte phenotype by negatively affecting the mitochondrial thermogenesis. (5th December 2019) - Ghnaimawi, Saeed; Baum, Jamie; Liyanage, Rohana; Huang, Yan
Abstract: Regarding the beneficial roles in fetal neurodevelopment, n-3 polyunsaturated fatty acids (PUFAs) are wildly used as dietary supplements during pregnancy. However, it may affect fetal and offspring muscle development and energy balance by changing the levels of key proteins controlling lipid metabolism and energy utilization. Regulation of energy balance in vivo is a topic of great interest and prominent goal for many studies. In this study, we focus on the effect of EPA and DHA on C2C12 brown adipogenic capacity. We demonstrated that the differentiation route of C2C12 into brown adipocytes was compromised by PUFA treatment through reducing their thermogenesis independent of UCP1 gene. This effect might be in part due to down-regulation of the expression of some brown adipocytes specific genes such as CP-3, DIO2, and PGC1α. Moreover, members of complex ІV (COX7a1 and COX8b) and complex V (ATP5j2) regulating ECT function were reduced in PUFA treated group. Also, mitochondrial biogenesis related genes including PGC1α, PGC1β, TFAM, and ERR-a were significantly suppressed by PUFA treatment. The mass spectrometric evaluation exhibited a strong correlation between PUFA treatment and the decreasing of levels of the proteins regulate Krebs cycle and ETC, such as ATP synthase α and β (F1F0 complex), citrate synthase, succinate CO-A, aconitate hydratase, and cytochrome c. Genomic and proteomic changes were accompanied by mitochondrial dysfunction represented by reducing oxygen consumption rate, ATP production, and proton leak (All statistically different at P < 0.05). In line with that, our results demonstrated an increase in lipid droplets size and number. EPA and DHA associated inhibition of the acquisition of functional brown adipocytes might negatively affect factor in the neonatal thermoregulation but potentially increase the intramuscular adipogenesis.